Colors and its relation with Depression - Mithali, Mehra (My University, 2017)
Colors have a great impact on our lives. The aim of the present study was to see the effect of level of depression on color choice and to study the association of emotions (positive and negative) on choosing different shades of color by different levels of depressed people. A total of 115 adults (including 37 males and 78 females) participated in the study. The age range was 18-25years. It was hypothesized that different levels of depression affects the color choice. It was also predicted that Individuals with high level of depression will associate dark shades with positive emotions and Individuals with high and low level of depression will associate dark shades with negative emotions. Beck’s Depression Inventory, Color preference test, negative emotion (sad, gloomy, depression, shame), positive emotion (joy, hope, happiness) were used in the present study. ANOVA and Regression were used to analyze the data. Findings of the study confirmed all the hypotheses. Findings are explained in terms of Beck, (1968) a depressed will tend to distort the world, irrespective of a happy or sad moment. Calculated results are beneficial for clinical settings.
Keywords: color, depression, emotions, BDI TEST, Color preference test.